PENGARUH MEDIA AUDIO VISUAL BERBASIS CANVA DALAM MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS V SEKOLAH DASAR - Senny Widia Oktari; Lina Indriani (STKIP Subang, 2024)
This study aims to determine the influence of canva-based audio-visual media in improving the learning outcomes of IPAS students in grade V of SDI Tebuireng Abdul Wahid Hasyim. This study uses quantitative research with a Pre-Experiment Design approach of the One Group Pre-Test Post-Test Design type. The researcher only used an experimental class without a control class to see the results in the pre-test and post-test as a benchmark for equality before and after treatment using canva-based audio-visual media. The population in this study is all students in grade V consisting of classes VA and VB. The technique in sample selection used is saturated sample. The sample to be used is the VA class with a total of 32 students. The validity test was used with the Pearson Product-Moment Correlation formula. Then the reliability test was continued with Cronbach's Alpha formula. The data in the research results were then tested for normality with the Kolmogorov-Smirnov test formula. For the T test, the Paired Sample T-Test was used at a significance level of α = 5% or α = 0.05 in the hypothesis test. Then to calculate how much impact audio visual media has on learning outcomes, researchers use the Size Effect test. The results of the study showed that the use of canva-based audio-visual learning media had a positive and significant influence on the learning outcomes of my pride area material in grade V students of SDI Tebuireng Abdul Wahid Hasyim.